The relation between NEAT1 expression level and survival rate in patients with oral squamous cell carcinoma - Nan-Chin Lin; Shih-Min Hsia; Tong-Hong Wang; Po-Jung Li; Yu-Hsin Tseng; Kuo-Chou Chiu; Hsi-Feng Tu; Yin-Hwa Shih; Tzong-Ming Shieh (Elsevier, 2022)
Background/purpose: Numerous studies have shown that long noncoding RNAs (lncRNAs) are involved in cancer progression and chemotherapy resistance. Nuclear enriched abundant transcript 1 (NEAT1) is an lncRNA. It affects tumor cell progression and drug resistance in various tumors. However, the relation of NEAT1 and survival rate in oral squamous cell carcinoma (OSCC) requires further study. Materials and methods: One normal gingival epithelium cell line, SG, three oral cancer cell lines (HSC3, OEC-M1, and SAS), 34 paired non-cancerous matched tissues (NCMT), and OSCC tissues were used in this study. Tri-reagent was used for total RNA extraction. NEAT1 expression was assessed by reverse transcription-quantitative PCR (RT-qPCR). Results: NEAT1 expression in oral cancer cell lines was lower than that in normal cells and was significantly downregulated in OSCC. NEAT1 upregulation reduced the survival rate of patients with OSCC. NEAT1 upregulation also reduced the survival rate of OSCC patients treated with chemotherapy and radiotherapy. Conclusion: These results indicate that NEAT1 expression is a valuable biomarker for the prediction and prognosis of oral cancer.